Occidental Petroleum's acquisition ofAnadarko : the stock market misapproves of Hollub's transformational deal - Elias, Jaan, (SAGE Business cases., 2021)
In May of 2019, Vicki Hollub, the CEO of Occidental Petroleum (Oxy), pulled off a blockbuster deal. Bidding against Chevron, one of the world's largest oil firms, she had managed to buy Anadarko, another oil company that was roughly the size of Oxy. Hollub believed that the combination of the two firms brought the possibility for billions of dollars in synergies, more than offsetting the cost of the acquisition. The deal would make Oxy the largest producer in what had become the world's richest oil field, the Permian Basin. However, shareholders disagreed and the price of Oxy dipped after the announcement of the deal and activist investors attempted to reign in management. The case invites students to consider the pros and cons of this acquisition and whether the purchase of Anadarko was a sound strategy for Oxy.